2014
DOI: 10.14740/jocmr1829w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Elevated Glycated Hemoglobin Concentrations in the Polycystic Ovary Syndrome: Anthropometrical and Metabolic Relationship in Amazonian Women

Abstract: BackgroundTo determine the prevalence of elevated glycated hemoglobin (HbA1c) and to examine its relationship with other carbohydrate metabolic parameter among Brazilian women with polycystic ovary syndrome (PCOS).MethodsA cross-sectional study including 288 PCOS patients was conducted. Anthropometrical, clinical, biochemical and endocrine parameters were evaluated.ResultsThe mean age was 26.92 ± 5.51 years. HbA1c mean concentration was 5.83±1.34%. In 38.54% of patients, HbA1c was ≥ 5.7%. HbA1c was positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Primary hypothyroidism was excluded by a thyroid-stimulating hormone (TSH) level of ≤4.2 µUI/mL and free thyroxin (fT4) level of ≤9.0 pmol/L (28,29). Hyperprolactinemia was excluded when prolactin (PRL) levels were ≤1.1 nmol/L (30). Before analysis PCOS patients were also stratified in categories according to age, as follows: younger than 19 years, 20 to 24 years, 25 to 29 years, 30 to 34 years, 35 to 39 years.…”
Section: Design Objective and Subjects Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Primary hypothyroidism was excluded by a thyroid-stimulating hormone (TSH) level of ≤4.2 µUI/mL and free thyroxin (fT4) level of ≤9.0 pmol/L (28,29). Hyperprolactinemia was excluded when prolactin (PRL) levels were ≤1.1 nmol/L (30). Before analysis PCOS patients were also stratified in categories according to age, as follows: younger than 19 years, 20 to 24 years, 25 to 29 years, 30 to 34 years, 35 to 39 years.…”
Section: Design Objective and Subjects Eligibilitymentioning
confidence: 99%
“…Blood samples were taken by cubital venipuncture between 7:30 and 10:00 h, after 10-12 h of fasting, between the third and fifth days of a spontaneous menstruation or, in the case of infrequent menses or amenorrhea, on any day regardless of the time elapsed since the last menstrual period; in this case, the progesterone (P4) level was used to certify that samples were collected in the follicular phase and the results were validated whenever the P4 level was lower than 6.3 nmol/L (30). A glucose oxidase technique (Beckman Glucose Analyses, Fullerton, CA, USA) was used to measure fasting glucose.…”
Section: Biochemical and Metabolic Measurementsmentioning
confidence: 99%
“…In a study by Sebastiao Medeiros et al; HbA1c was raised in 38% PCOS patients; 35% with prediabetes and 3% with diabetes. 7 Jin Ju Kim et al found 31.2% prevalence of raised HbA1c in PCOS women. 13 de Medeiros SF et al, found that HbA1c was raised in 46 % of PCOS women.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account this potential association between HbA1c and health consequences in PCOS patients, the current study aimed to estimate the prevalence of elevated HbA1c in PCOS women in our institute. 7 PCOS is characterized by increased activation of the inflammatory system stemming from insulin resistance, which predicts future cardiovascular risk. 8 IR elevates several proinflammatory mediators, which leads to endothelial dysfunction, reduced vasoreactivity, and subclinical atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…After standardization of the diagnostic criteria for polycystic ovary syndrome (PCOS) the hyperandrogenemic phenotype has been found in nearly 80% of patients ( 1 , 2 ). These hyperandrogenemic patients may have their androgen synthetized by ovaries, adrenal gland, or both.…”
Section: Introductionmentioning
confidence: 99%